Withaferin A suppresses the growth of myelodysplasia and leukemia cell lines by inhibiting cell cycle progression. Issue 9 (28th July 2016) - Okamoto, Shuichiro; Tsujioka, Takayuki; Suemori, Shin‐ichiro; Kida, Jun‐ichiro; Kondo, Toshinori; Tohyama, Yumi; Tohyama, Kaoru
Abstract : Treatment outcomes for acute myeloid leukemia and myelodysplastic syndromes (MDS) remain unsatisfactory despite progress in various types of chemotherapy and hematopoietic stem cell transplantation. Therefore, there is a need for the development of new treatment options. We investigated the growth‐suppressive effects of withaferin A (WA), a natural plant steroidal lactone, on myelodysplasia and leukemia cell lines. WA exhibited growth‐suppressive effects on the cell lines, MDS‐L, HL‐60, THP‐1, Jurkat and Ramos, and induction of cell cycle arrest at G2/M phase at relatively low doses. Evaluation by annexin V/PI also confirmed the induction of partial apoptosis. Gene expression profiling and subsequent gene set enrichment analysis revealed increased expression of heme oxygenase‐1 ( HMOX1 ). HMOX1 is known to induce autophagy during anticancer chemotherapy and is considered to be involved in the treatment resistance. Our study indicated increased HMOX1 protein levels and simultaneous increases in the autophagy‐related protein LC3A/B in MDS‐L cells treated with WA, suggesting increased autophagy. Combined use of WA with chloroquine, an autophagy inhibitor, enhanced early apoptosis and growth suppression. Together with the knowledge that WA had no apparent suppressive effect on the growth of human normal bone marrow CD34‐positive cells in the short‐term culture, this drug may have a potential for a novel therapeutic approach to the treatment of leukemia or MDS. Abstract : Withaferin A exhibited growth‐suppressive effects on MDS/leukemia cell lines and induction of cell cycle arrest at G2/M phase. Gene expression profiling and subsequent gene set enrichment analysis (GSEA) revealed increased expression of heme oxygenase‐1 . As withaferin A had no apparent suppressive effect on the growth of human normal bone marrow CD34‐positive cells, this drug may have a potential for a novel therapeutic approach to the treatment of leukemia or MDS.